Consumer's environmental awareness and the role of (green) entrepreneurship: Lessons from environmental quality competition and R&D activities for environmental policy - Torben Klarl (Universität Augsburg, Institut für Volkswirtschaftslehre, 2013)
In the recent last years, in particular in the aftermath of the global financial and economic crisis, many countries initiated economic recovery plans with a major focus on stimulating green entrepreneurial activities to revive economic growth. Further, the recovery plans intend to improve a country's awareness for a direct orientation towards (strong) sustainability and green growth. Before discussing strategies towards green growth, in this paper we propose a novel framework to increase our understanding of the interplay of process R&D activities, the strategic price and environmental quality setting of heterogeneous entrepreneurs in a market where consumers feel up to paying for environmental quality improvement of a vertically differentiated good. In the paper we decompose an entrepreneur's incentive conducting process R&D in four parts. In particular we show that an entrepreneur's incentive of conducting own process R&D is reduced due to the existence of knowledge-spillovers. Moreover, due to the strategic complementarities, both in prices as well as in environmental quality, a strategic effect reinforces the negative consequences of the spillover-effect. We show that the externalities in the model require corrections based upon a mixture of fiscal policies and a process R&D subvention scheme establishing a first-best solution. We further thoroughly discuss the implementation of a second-best solution and derive environmental policy implications.
urn:nbn:de:bvb:384-opus4-710960
Keywords: Q55; Q58; O31; O33; D43; L13; L15; 330; Technological change; Process R&D; Green consumerism; Vertical differentiation; Emission tax; Environmental quality; Environmental policy